The very low genetic variability on Aceh Tamiang’s (Indonesia) population of Painted Terrapin (Batagur borneoensis) inferred by cytochrome oxidase I (CO I) and D-loop (control region) - JOKO GUNTORO; WIRDATETI; AWAL RIYANTO (Society for Indonesian Biodiversity, 2020)
Abstract. Guntoro J, Wirdateti, Riyanto A. 2020. The very low genetic variability on Aceh Tamiang’s (Indonesia) population of Painted Terrapin (Batagur borneoensis) inferred by cytochrome oxidase I (CO I) and D-loop (control region). Biodiversitas 21: 2514-2520. Populations of Batagur borneoensis have been rapidly decreasing due to the harvesting of adults and eggs for food and the construction of beachfront property causing the loss of nesting areas. By the new Indonesian regulation, since 2018 this turtle listed in the protected animal. Meanwhile, IUCN placed as critically endangered which indicating a high risk of extinction in the wild in the near future (www.iucnredlist.org). We used cytochrome oxidase I (COI) and control region D-loop region to investigate intraspecific variations on Aceh Tamiang’s population of painted terrapin, Batagur borneoensis. DNA material was gathered from saliva collected from 90 juveniles in the reaching facility of Sukacita Lestari Indonesia Foundation which hatched from eggs collected from December 2015 to April 2016 from 30 nests on beach area at Aceh Tamiang. The population showed very low genetic variability (haplotype diversity, Hd = 0.457 based on COI and 0.405 based on D-loop; nucleotide diversity, ? = 0.00089 based on COI and 0.00076 based on D-loop). So, we suggested that further study such as more exploration to find new wild populations and genetic study across wild populations should be done to reveal genetic variability and genetic structure which important to decide the conservation strategy. At the time for Aceh Tamiang's population, the ranching conservation program should be maintained at least to keep the successful hatchling from hunters and natural predators both during eggs laying and hatching.